2015
DOI: 10.1016/j.jad.2015.01.021
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal proton magnetic resonance spectroscopy study investigating oxidative stress as a result of alcohol and tobacco use in youth with bipolar disorder

Abstract: Alcohol and tobacco have been suggested to be "aggravating factors" for neuroprogression in bipolar disorder (BD), however the impact of these substances on the underlying neurobiology is limited. Oxidative stress is a key target for research into neuroprogression in BD and in accordance with this model, our previous cross-sectional studies have found that risky alcohol and tobacco use in BD is associated with increased oxidative stress, investigated via in vivo glutathione (GSH) measured by proton magnetic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 47 publications
2
13
0
2
Order By: Relevance
“…We concluded that this highlights that people with BD are be more susceptible to the oxidative effects of alcohol. Our longitudinal data demonstrates that patients who decreased their drinking after 18 months had an associated increase in GSH, which was supported by the regression model, showing that decrease in alcohol consumption was a significant predictor of increased GSH at follow-up (Chitty et al, 2015a). Importantly these findings suggest that the oxidative effects of alcohol in youth with BD are potentially reversible with a reduction in drinking.…”
Section: Glutathione Bipolar Disorder and Alcoholsupporting
confidence: 80%
See 3 more Smart Citations
“…We concluded that this highlights that people with BD are be more susceptible to the oxidative effects of alcohol. Our longitudinal data demonstrates that patients who decreased their drinking after 18 months had an associated increase in GSH, which was supported by the regression model, showing that decrease in alcohol consumption was a significant predictor of increased GSH at follow-up (Chitty et al, 2015a). Importantly these findings suggest that the oxidative effects of alcohol in youth with BD are potentially reversible with a reduction in drinking.…”
Section: Glutathione Bipolar Disorder and Alcoholsupporting
confidence: 80%
“…It is important to re-state here, that in our follow-up study an increase of GSH was found with a decrease in drinking and smoking in BD (Chitty et al, 2015a), suggesting that in the context of the BD-alcohol comorbidity the first line treatment in reducing oxidative stress should be to reduce alcohol consumption and tobacco use.…”
Section: Pharmacological Implications From Proposition 2: Neuroprotecmentioning
confidence: 59%
See 2 more Smart Citations
“…Promena u potrošnji alkohola, zatim duvana, kao i godine starosti, bili su značajni prediktori promena u koncentraciji GSH. Ova studija pruža dokaz da je korekcija rizičnih obrazaca za piće i duvan u ranoj fazi BP, povezana sa poboljšanjima u sferi antioksidativnog kapaciteta, a samim tim to mogu da budu specifični ciljevi za ranu intervenciju i prevenciju neuroprogresije u bipolarnom poremećaju [31].…”
Section: Najnovija Istraživanja Komorbiditeta Bolesti Adikcije I Drugunclassified